The bird remains from Saruq al-Hadid: Insights into human activity and the environment in late prehistoric southeastern Arabia. (30th March 2020) - Roberts, James; Weeks, Lloyd; Fillios, Melanie; Cable, Charlotte; Yousef al-Aali, Yaaqoub; Boraik, Mansour; Zein, Hassan
Abstract: Excavations at Saruq al-Hadid, a late prehistoric (c.2000 BCE – c.800 BCE) site located in the Emirate of Dubai, U.A.E., have recovered several tonnes of animal bone. Due to a thorough sieving and retention strategy the remains of a range of taxa were collected, from camels to rodents. Within this wealth of material several dozen fragments of a variety of bird species were identified that have given a unique insight into human activity in the interior of southeastern Arabia; from sea birds (an unexpected find, given that the site is 40 km away from the current coastline), to a fragment of raptor that might reflect early hunting practices. The presence of certain bird species in the remains may also be indicative of the site's past environment and suggests it was likely different to the sparsely vegetated mobile dune field it is today. This paper outlines these remains, from their excavation to their analysis. The insights they provide into the nature of the occupation at Saruq al-Hadid are discussed, thereby demonstrating the great utility of studying even a relatively small assemblage of archaeological bird remains.